IMPLIKASI MEDIA SOSIAL FACEBOOK TERHADAP KEHARMONISAN KELUARGA DI DESA KORLEKO KECAMATAN LABUHAN HAJI LOMBOK TIMUR - Nasrul Hadi (Universitas Hamzanwadi, 2020)
Social media Facebook is a social networking website where the users can join the community such as city, work, school and areas for connecting and interacting with people other. Facebook is also a medium for making friends, sending messages and add a photo as a symbol of themselves so that they can be recognized by other people. There are many different purposes for people to access. Facebook social media to make it easier to communicate then usually used as a place to pour feelings and content his heart, looking for new acquaintances, looking for life partners and ones most importantly used as a source of inspiration, and education within carry on a daily routine.